1998
DOI: 10.1111/j.1365-2109.1998.tb01106.x
|View full text |Cite
|
Sign up to set email alerts
|

Changes in shell dimensions of pearl oysters, Pinctada mazatlanica (Hanley 1856) and Pteria sterna (Gould 1851), during growth as criteria for Mabé pearl implants

Abstract: The relationship between the shell dimensions of pearl oysters. Pinctada nmzallaiiica (Hanley 1856) and Pteria sterna (Gould lHSl), was studied to determine the possible change of form of Ihc shell during growth. The intention was to delermine the number, size and location of nuclei that could be implanted in oysters used for Mabe pearl production. Using the database of our Pearl Culture Research Programme developed in Bahia de La Paz. Mexico, we obtained measurements of 500 shells of P. mazatlaniai and 500 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
37
0
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(40 citation statements)
references
References 10 publications
2
37
0
1
Order By: Relevance
“…For example, Alagarswami and Chellam (1977) found that young ( Ͻ 36 mm) Akoya pearl oysters changed from a sub-quadrate shape to an oblong shape. Similarly, P. mazatlanica was reported to undergo isometric growth up to a size of around 100 mm when shape began to change from being " symmetrical " to " oblong " ( Saucedo et al , 1998 ). Strong variation in shell morphology was reported for Pt.…”
Section: Shell Dimensions and Morphometricsmentioning
confidence: 95%
See 2 more Smart Citations
“…For example, Alagarswami and Chellam (1977) found that young ( Ͻ 36 mm) Akoya pearl oysters changed from a sub-quadrate shape to an oblong shape. Similarly, P. mazatlanica was reported to undergo isometric growth up to a size of around 100 mm when shape began to change from being " symmetrical " to " oblong " ( Saucedo et al , 1998 ). Strong variation in shell morphology was reported for Pt.…”
Section: Shell Dimensions and Morphometricsmentioning
confidence: 95%
“…Galtsoff, 1931 ;Alagarswami and Chellam, 1977 ;Yoo et al ., 1986 ;Gaytan-Mondragon et al ., 1993 ;Southgate and Beer, 1997 ;Saucedo et al , 1998 ). Such data can be used in assessing the effects of different growth conditions and to describe ontogenetic changes ( Gervis and Sims, 1992 ).…”
Section: Shell Dimensions and Morphometricsmentioning
confidence: 99%
See 1 more Smart Citation
“…We used shell volume (cm 3 ) and mortality incidence (%) as indicators for treatment evaluation. Shell volume allowed more consistent interpretation of growth trends in P. mazatlanica (Saucedo et al 1998;Monteforte and Morales 2000).…”
Section: Introductionmentioning
confidence: 96%
“…In the Pteriidae family (pearl oysters), growth and age have been studied for the main pearl producing species, including Pinctada fucata (Pandya 1976;Chellam 1978;Velayudhan et al 1996), P. margaritifera (Southgate and Beer 2000;Pouvreau et al 2000), P. maxima (Gervis and Sims 1992;Lee et al 2008), P. mazatlanica (Gaytán-Mondragón et al 1993;Monteforte and Garcia-Gasca 1994;Saucedo and Monteforte 1997a;Saucedo et al 1998), and Pteria sterna (Araya-Núñez et al 1991;Bückle-Ramírez et al 1992;Del Rio-Portilla et al 1992;Monteforte et al 1995). In most of these studies, age estimations were made by assigning an average date at the moment when spat were separated from artificial collectors and tagged prior to starting the nursery period.…”
Section: Introductionmentioning
confidence: 99%